1981
DOI: 10.1098/rsta.1981.0063
|View full text |Cite
|
Sign up to set email alerts
|

Back-arc extension in the Scotia Sea

Abstract: The nature of back-arc extension in the East Scotia Sea is re-examined with the use of an enlarged geophysical data set. Well developed oceanic magnetic lineations confirm that the present spreading episode started about 8 Ma ago, that spreading is asymmetric, and that the total rate increased from 50 to 70 m m /a about 1.5 Ma ago. Most of the currently active South Sandwich volcanic island arc lies upon ocean floor only 6-8 M a old and generated at the current spreading ridge. Subsequent extension has not mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(33 citation statements)
references
References 6 publications
1
32
0
Order By: Relevance
“…The South Sandwich Arc is entirely intra-oceanic, far-removed from any continental crust and, on the basis of magnetic anomalies, is situated on 10 Ma old oceanic crust of the Sandwich Plate (Barker and Hill 1981). A new multichannel seismic reflection survey identified arc-ward tilted blocks in the mid-forearc indicating large scale gravitational collapse, consistent with earthquake data indicating normal extension at shallow depth in this area (Vanneste et al 2002).…”
Section: South Sandwich Subduction Zonesupporting
confidence: 56%
“…The South Sandwich Arc is entirely intra-oceanic, far-removed from any continental crust and, on the basis of magnetic anomalies, is situated on 10 Ma old oceanic crust of the Sandwich Plate (Barker and Hill 1981). A new multichannel seismic reflection survey identified arc-ward tilted blocks in the mid-forearc indicating large scale gravitational collapse, consistent with earthquake data indicating normal extension at shallow depth in this area (Vanneste et al 2002).…”
Section: South Sandwich Subduction Zonesupporting
confidence: 56%
“…Moreover, rifting rates on the east Scotia Ridge remain fairly constant along its length (6-7 cm/a) supporting the assertion that the Sandwich Plate rotates about a distant pole relative to the Scotia Plate [Thomas et al, 2003]. The dominant influence on Scotia Basin rifting is likely to be rollback of the subducting South American slab [Barker and Hill, 1981;Barker et al, 1991]. The slab subducting beneath the South Sandwich arc is quite narrow ($600 km wide, in the alongstrike direction) in comparison to other subducting slabs which are typically 1000s of km wide.…”
Section: A324 Philippinesmentioning
confidence: 60%
“…6 Ma ago (coinciding with reinitiation of Nankai Trough subduction [Kamata and Kodama, 1994]) [Barker and Hill, 1981] No [Skerlec and Hargraves, 1980] Bering Sea North of western AleutiansEocene-Oligocene/Miocene [Worrall, 1991] [Zhou et al, 1995] None apparent None apparent Uncertain South Fiji Basin Australia/New Zealand region ( Tasman Sea) 25 -34 Ma ago [Watts et al, 1977;Malahoff et al, 1982b] None apparent None apparent…”
Section: Part Of the North Fiji Basin Vanuatumentioning
confidence: 99%
“…The distribution of plate boundaries in the region together with their motion is summarised by BARKER and DALZIEL (1980) and by BARKER and HILL (1981) as shown in Fig. 1.…”
Section: Tectonic Relationshipsmentioning
confidence: 99%
“…The Scotia Sea is thought to have formed over the past 40Ma as an increasingly intricate modification of the South American (SAM) and Antartic (ANT) plate boudaries. Marine geophysical investigations (BARKER, 1972;BARKER and HILL, 1981) have shown that active sea-floor spreading is taking place some 440km west of the South Sandwich Trench. Such back-arc extension has given rise to the Scotia and Sandwich plates as defined by BARKER and DALZIEL (1980).…”
Section: Tectonic Relationshipsmentioning
confidence: 99%